Exploring the optical properties of molybdenum trioxide: approach of theory modeling and depositions techniques - A. V. Juan-Arturo; A. Leonel Mendoza-Martínez; Gesuri Morales-Luna; Michael Morales-Luna (Advances in Physics: X)
The study of Transition Metal Oxides (TMOs) has expanded in recent years because of their interesting electronic, mechanical, and chemical properties and extensive applicability in electronics and optoelectronics. One such material is trioxide molybdenum (MoO3), which has been used in novel applications in recent years. Beyond its applications, the theoretical understanding of MoO3 is crucial, as it provides deeper insight into the material’s behavior and could aid in predicting its performance in different applications. This review article presents the most recent known information about the optical properties, growing techniques, and applications of MoO3 nanostructures and thin films, emphasizing how these findings and theoretical advances can guide future research. Hence, any researcher has a more accessible and efficient way to understand further and exploit this promising material and its optical properties.